The Influence of Lifestyle, Income, and Perception of Paylater Use on Financial Behavior of Gen Z in Mataram City - Husniah Azriani; Burhanudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of lifestyle, income, and perception of paylater usage on the financial behavior of Gen Z in Mataram City, where the Gen Z population has reached 109,600 people with an increasing paylater trend. The aim is to analyze the influence of these three variables empirically. Using a quantitative associative causality approach with PLS-SEM, the Gen Z population aged 17-28 years was sampled with 120 respondents through proportional purposive sampling per sub-district. The 5-point Likert questionnaire instrument measured 24 indicators, analyzed with SmartPLS including outer/inner models, R², and bootstrapping 5,000 subsamples. The results show that lifestyle has a significant positive effect (β = 0.802, p = 0.027), paylater perception has a significant positive effect (β = 0.754, p = 0.040), while income is insignificant (β = 0.041, p = 0.202), with R² = 64.6%. The conclusion recommends fintech education and lifestyle control for Gen Z's financial stability